Next Generation Sequencing in Cytopathology: Focus on Non-Small Cell Lung Cancer - Pisapia, Pasquale; Pepe, Francesco; Iaccarino, Antonino; Sgariglia, Roberta; Nacchio, Mariantonia; Conticelli, Floriana; Salatiello, Maria; Tufano, Rossella; Russo, Gianluca; Gragnano, Gianluca; Girolami, Ilaria; Eccher, Albino; et al. (Frontiers in Medicine, 2021)
Molecular cytopathology is a rapidly evolving field embracing both conventional microscopy and molecular pathology. Its growing popularity stems from the fact that in many types of advanced cancers, including non small cell lung cancer (NSCLC), cytological samples often constitute the only available specimens for morphomolecular analysis. Indeed, non formalin fixed and paraffin embedded (FFPE) cytological samples feature a higher quality of extracted nucleic acids than histological specimens. However, because of the growing complexity of molecular testing, several efforts should be made to validate the analytical performance of the wide array of currently available molecular technologies, including next generation sequencing (NGS). This technology has the terrific advantage of allowing simultaneous detection of scores of predictive biomarkers even in low-input DNA/RNA specimens. Here, we briefly review the role of the modern cytopathologist in the morphomolecular diagnosing of advanced stage NSCLC and the adoption of NGS in conventional cytopreparations (cell blocks, direct smears, and liquid-based cytology) and supernatants.